Penambahbaikan Persijilan Blue Ribbon dengan Penambahan Nilai Kemanusiaan (TFI Buddies) (Improvement of Blue Ribbon Certification by Including Humanistic Value (TFI Buddies) / Siti Munira Yasin ...[et al.] - Yasin, Siti Munira; Mad Hisma, Harizah; Omar, Mazlifah; Ismail, Nurhuda; Izuan Azhar, Zahir; Omar, Zalina; Ismail, Ilham Ameera; Ruslan, Nur-Hasanah; Jamil, Shahizan; Md Shah, Nur Fazlinda; Suddin, Leny Suzana (Universiti Teknologi MARA, 2020)
Cigarette smoke produces more than 4,000 toxic chemicals and 53 of these chemicals can cause cancer. Smoking increases your health risks such as lung cancer, heart attack and stroke. In Malaysia, between 10% and 12% of causes of death are caused by smoking and this results in over 10,000 deaths a year. According to the National Health Morbidity Survey (NHMS) in 2015, the number of smokers aged 15 and above in Malaysia is estimated to be more than 5 million (22.8%). This alarming amount will lead to increased health costs. Smoking can also lead to a reduction in worker productivity and air pollution and the pollution due to cigarette smoke. Therefore, smokers need to be aware of the effects of smoking habits and the importance of maintaining a tobacco-free environment for the health and well-being of their families, friends and the community around them. To address this, Smoke Busters have created an innovation called Blue Ribbon Star Certification with an additional component of humanization into the TFI Buddies existing Blue Ribbon Certification. The main goal of this innovation is to make University of Technology MARA (UiTM) campuses 100% tobacco free. The first project at the Sungai Buloh Campus resulted in a decrease in the percentage of 'hotspots', whereby the number of cigarette butts was found to be greatly reduced. In addition, the percentage of staff with good knowledge and attitude on the effects of cigarettes increased. Feedback from users comprising staff and students also showed a very positive response. The direct impact on faculty and campuses include cost savings in terms of medical expenses and increase in staff productivity. The long-term effects include enhancing UiTM's image nationally and internationally. From a social point of view, this in addition creates a more caring and responsible generation of colleagues and the environment.